The Adaptation of the Mathematics Teachers’ Beliefs Scale into Turkish: Validity and Reliability Study - Kükey, Ebru (My University, 2023)
The purpose of this research is to analyze the validity and reliability of the Mathematics Teachers Belief Scale developed by Xie and Cai (2021) for its adaptation to Turkish culture and Turkish language. The study was designed as a mixed pattern. The study group consisted of 431 teachers of mathematics working in various cities of Turkey. The original scale is a 4-point Likert scale. It consists of 26 items in 5 subscales. Translation studies were carried out for the language validity of the scale. Then, exploratory factor analysis was performed with the examined data set. Analysis of the results showed that the original structure of the scale was preserved. Confirmatory factor analysis results, it was concluded that the scale structure had good or acceptable fit indexes. In addition, the t-values for the comparison of the item-total correlation coefficients and the 27% lower/upper group averages also provide data on the scale structure. Regarding reliability, Cronbach Alpha and Spearman-Brown two-half test reliability coefficients showed that the scale had a reliable structure. Result of analysis, sufficient evidence was obtained that the scale, which was adapted into Turkish, has a valid and reliable structure.
Keywords: Eğitim; Eğitim Araştırmaları